A method for preparing tin-based oxyfluoride compound
By using corundum tube sealing and molten salt treatment during the synthesis of tin-based fluorine compounds, the problems of tin volatility, fluoride reaction and low crystallinity are solved, and its photocatalytic activity is significantly improved.
Patent Information
- Application Number
- CN202310037181.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-01-10
AI Technical Summary
During the synthesis process, existing tin-based fluorine compounds are prone to volatile tin elements, reaction of fluoride with quartz glass, and insufficient photocatalytic activity due to low crystallinity.
After mixing the raw materials SnO, SnF2, TiO2 and Nb2O5, ethanol or deionized water is added for milling, then calcined in a quartz glass tube containing corundum tube and treated with molten salt to improve crystallinity.
It effectively reduces the volatility and disproportionation of tin elements, avoids the reaction of fluoride with quartz glass, improves the crystallinity of tin-based oxygen fluorine compounds, and thus enhances its activity as a water decomposition photocatalyst.
Smart Images

Figure CN115974155B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material synthesis and renewable clean energy utilization. Specifically, the present invention relates to a photocatalytic material, and more specifically, the present invention relates to a class of tin-based oxyfluoride compounds and preparation methods and applications thereof. Background Art
[0002] As the use of large amounts of fossil fuels has caused increasing energy consumption and environmental problems, decomposing water into hydrogen and oxygen is one of the most important ways to solve the future shortage of fossil fuels and reduce environmental pollution associated with fossil fuel consumption. Water decomposition consists of two half reactions, namely the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER).
[0003] The conversion efficiency of solar energy to hydrogen energy depends on the product of the light absorption efficiency, charge separation efficiency and surface catalytic reaction efficiency of semiconductor photocatalytic materials. Among them, wide-spectrum light absorption is the basis for achieving efficient solar energy conversion and has great practical significance. Traditional strategies for regulating the light absorption of metal oxide photocatalytic materials mainly include metal cation doping, non-metal anion doping, construction of solid solution, surface disordering and plasma resonance. Among them, non-metal anion doping is the most widely used strategy. Its main principle is to use the p orbital of non-metal ions with weaker electronegativity (compared to oxygen) to hybridize with O 2p orbitals, narrow the band gap and achieve a wide spectrum response. In addition, people often use metals containing lone pairs of electrons (Bi 3+ , Sn 2+ , Pb 2+ , Ag + )'s outermost s orbital hybridizes with the O 2p orbital, shortening the band gap and producing a visible light response.
[0004] The related art discloses oxyhalogen compounds with wide spectral response, such as Bi4NbO8Cl, Bi2MO4Cl (M = Bi, Y, La, etc.), Ba2Bi3Nb2O 11 I and other compounds, as well as Pb2Ti2O 5.4 F 1.2 , Pb2Ti4O9F2 and other compounds. The hybridization of Bi 6s orbital, Pb 6s orbital and O 2p orbital in bismuth-based compounds and lead-based compounds can produce wide-spectrum response photocatalysts. Similarly, the hybridization of Sn 5s orbital and O 2p orbital in tin-based compounds can also produce visible light response photocatalysts, such as Sn2Nb2O7, SnNb2O6, etc. Through the modified lone pair electron theory, the degree of hybridization of Sn 5s orbital and O 2p orbital can be determined according to the degree of crystal structure distortion: the greater the lattice distortion, the stronger the hybridization of Sn 5s orbital and O 2p orbital.
[0005] Using the strategy of replacing oxygen atoms with fluorine atoms, the synthesis of tin-based compounds with different chemical compositions is expected to obtain new photocatalysts with wide spectral response. The tin-based oxyfluoride compounds reported in the related art have one or more of the following problems:
[0006] (1) Certain volatile elements, such as tin, easily volatilize to form Sn 0 With Sn 4+ , resulting in the synthetic sample containing elemental tin and high-valent tin atoms.
[0007] (2) The catalyst sample is placed in a quartz glass tube to synthesize the corresponding oxyfluoride compound. The fluoride will react with SiO2 to generate corresponding impurities, resulting in the impure synthesized sample.
[0008] (3) The tin-based oxyfluoride compounds prepared in the related art have low crystallinity, which in turn affects their photocatalytic activity. Summary of the invention
[0009] The present invention aims to solve at least one of the technical problems existing in the above-mentioned related technologies. To this end, an embodiment of the present invention provides a method for preparing a tin-based oxyfluoride compound.
[0010] Another aspect of the present invention provides a tin-based oxyfluoride compound prepared by the method of the present invention and its use as a photocatalyst for decomposing water.
[0011] A method for preparing a tin-based oxyfluoride compound according to an embodiment of the present invention comprises the following steps:
[0012] S1: Mix the raw materials SnO, SnF2, TiO2 and Nb2O5, add ethanol or deionized water, and grind them evenly to obtain a raw material mixture;
[0013] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 500-800° C. for calcining for 5-10 hours;
[0014] S3: subjecting the product of step S2 to molten salt treatment to obtain the tin-based oxyfluoride compound.
[0015] In some embodiments, the molar ratio of the raw materials SnO, SnF2, TiO2 and Nb2O5 in step S1 is 3:(1.05-1.2):2:1.
[0016] In some embodiments, the raw materials of step S1 also include NaF, and the molar ratio of the raw materials NaF, SnO, SnF2, TiO2 and Nb2O5 is (2.1-2.2):1:(1.05-1.1):2:1.
[0017] In some embodiments, the milling time of step S1 is 30 min to 60 min.
[0018] In some embodiments, the molten salt treatment is carried out at a temperature of 300 to 400° C., for a treatment time of 24 to 48 hours, in an Ar gas atmosphere.
[0019] In some embodiments, the molten salt of the molten salt treatment is selected from at least one of KNO3, KCl, NaNO3, and NaCl.
[0020] In some embodiments, the molar ratio of the product of step S2 to the molten salt is 1:(5-10).
[0021] In some embodiments, step S3 further comprises washing the sample treated with molten salt with water and then drying it to obtain a finished tin-based oxyfluoride compound.
[0022] The embodiment of the present invention also provides a tin-based oxyfluoride compound prepared by the above preparation method.
[0023] The embodiment of the present invention also provides the use of the above-mentioned tin-based oxyfluoride compound as a water decomposition photocatalyst.
[0024] The embodiments of the present invention have the following beneficial effects:
[0025] (1) In the method of the embodiment of the present invention, the corundum tube is sealed in a quartz glass tube, the raw material mixture is placed in the corundum tube, the quartz glass tube is sealed to ensure its vacuum environment, the corundum tube ensures that the fluoride does not react with the quartz glass SiO2 during the reaction process, ensures that there are no impurities in the synthesized sample, and the fluorine element is retained to the greatest extent.
[0026] (2) For tin-based oxyfluoride compounds, the tin element is also easy to volatilize and undergo a disproportionation reaction to generate a +4-valent tin element. The method of the embodiment of the present invention can effectively reduce the disproportionation reaction of the tin element and reduce the defect density of the photocatalyst.
[0027] (3) The method of the embodiment of the present invention adopts molten salt treatment, which can improve the crystallinity of the synthesized tin-based oxyfluoride compound and effectively improve the photocatalytic reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0029] Figure 1 The following is a flow chart of the preparation of the tin-based oxyfluoride compound according to an embodiment of the present invention;
[0030] Figure 2 XRD diagrams of STNOF samples synthesized by different preparation methods in the embodiments of the present invention and comparative examples;
[0031] Figure 3 XRD refined image; (space group: Rwp=5.93%,Rp=4.09%,χ 2 =5.21);
[0032] Figure 4 UV-Vis images of STNOF samples synthesized by different preparation methods in the embodiments of the present invention and comparative examples;
[0033] Figure 5 The pictures of STNOF samples synthesized by different preparation methods in the embodiments and comparative examples of the present invention;
[0034] Figure 6 The activity diagrams of STNOF samples synthesized by different preparation methods in the examples and comparative examples of the present invention are shown.
[0035] in:
[0036] STNOF-none is a STNOF sample prepared by passing inert gas in Comparative Example 1;
[0037] STNOF-SiO2 is a STNOF sample prepared by placing the raw material mixture in a quartz glass tube in Comparative Example 2;
[0038] STNOF-Al2O3 is the product of step S2 of Example 1, i.e., a STNOF sample prepared by placing the raw material mixture into a quartz glass tube with a corundum tube;
[0039] STNOF-Al2O3-M is the product of step S3 of Example 1, that is, the raw material mixture is placed in a quartz glass tube with a corundum tube, calcined, and then subjected to molten salt treatment to prepare the STNOF sample. DETAILED DESCRIPTION
[0040] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0041] Figure 1 The flow chart of the preparation of the tin-based oxyfluoride compound (catalyst) of the embodiment of the present invention is shown. First, the catalyst raw materials are mixed and ground in a mortar, and then added into the corundum tube of the quartz glass tube with a built-in corundum tube through a funnel. Then, the small diameter side of the quartz glass tube is calcined and sealed, and the catalyst sample (STNOF sample) is prepared after the reaction. Specifically,
[0042] A method for preparing a tin-based oxyfluoride compound according to an embodiment of the present invention comprises the following steps:
[0043] S1: Mix the raw materials SnO, SnF2, TiO2 and Nb2O5, add ethanol or deionized water, and grind them evenly to obtain a raw material mixture;
[0044] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 500-800° C. for calcining for 5-10 hours;
[0045] S3: subjecting the product of step S2 to molten salt treatment to obtain the tin-based oxyfluoride compound.
[0046] For non-limiting example, the calcination temperature of step S2 can be 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, etc., and the calcination time can be 5h, 6h, 6.5h, 7h, 8h, 10h, etc.
[0047] The method of the embodiment of the present invention seals the corundum tube in a quartz glass tube, the raw material mixture is placed in the corundum tube, the quartz glass tube is sealed to ensure its vacuum environment, the corundum tube ensures that the fluoride does not react with the quartz glass SiO2 during the reaction process, ensures that there are no impurities in the synthesized sample, and the fluorine element is retained to the greatest extent. The method of the embodiment of the present invention can effectively reduce the disproportionation reaction of the tin element and reduce the defect density of the photocatalyst.
[0048] In some embodiments, the molar ratio of the raw materials SnO, SnF2, TiO2 and Nb2O5 in step S1 is 3: (1.05-1.2): 2: 1. Non-limiting examples include: the molar ratio can be: 3: 1.05: 2: 1 or 3: 1.08: 2: 1 or 3: 1.1: 2: 1 or 3: 1.12: 2: 1 or 3: 1.2: 2: 1, etc.
[0049] In some embodiments, the raw materials of step S1 further include NaF, and the molar ratio of the raw materials NaF, SnO, SnF2, TiO2 and Nb2O5 is (2.1-2.2): 1: (1.05-1.1): 2: 1. Non-limiting examples include: the molar ratio can be: 2.1: 1: 1.05: 2: 1 or 2.12: 1: 1.06: 2: 1 or 2.14: 1: 1.07: 2: 1 or 2.16: 1: 1.08: 2: 1 or 2.18: 1: 1.09: 2: 1 or 2.2: 1: 1.1: 2: 1, etc.
[0050] In some embodiments, the milling time of step S1 is 30 min to 60 min. For example, the milling time of step S1 can be 30 min, 35 min, 40 min, 45 min, 50 min, 60 min, etc.
[0051] In some embodiments, the temperature of the molten salt treatment is 300-400°C, the treatment time is 24-48h, and the Ar gas atmosphere is used. Non-limiting examples include: the temperature of the molten salt treatment can be 300°C, 320°C, 340°C, 350°C, 380°C, 400°C, etc., and the treatment time can be 24h, 26h, 30h, 35h, 40h, 48h, etc. The method of the embodiment of the present invention adopts molten salt treatment, which can improve the crystallinity of the synthesized tin-based oxyfluoride compound and effectively improve the photocatalytic reaction activity.
[0052] In some embodiments, the molten salt of the molten salt treatment is selected from at least one of KNO3, KCl, NaNO3, and NaCl.
[0053] In some embodiments, the molar ratio of the product of step S2 to the molten salt is 1:(5-10). Non-limiting examples include: the molar ratio may be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.
[0054] In some embodiments, step S3 further comprises washing the sample treated with molten salt with water and then drying it to obtain a finished tin-based oxyfluoride compound.
[0055] In some embodiments, the drying temperature is 70-80° C., and the drying time is 12-15 hours. Non-limiting examples include: the drying temperature can be 70° C., 72° C., 74° C., 75° C., 78° C., 80° C., etc., and the drying time can be 12 hours, 12.5 hours, 13 hours, 14 hours, 14.5 hours, 15 hours, etc.
[0056] The embodiment of the present invention also provides a tin-based oxyfluoride compound prepared by the above preparation method.
[0057] The embodiment of the present invention also provides the use of the above-mentioned tin-based oxyfluoride compound as a water decomposition photocatalyst.
[0058] The following are non-limiting examples of the present invention. It should be noted that in the application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made by commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0059] Example 1
[0060] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0061] S1: 0.404 g SnO (3 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 40 min to obtain a raw material mixture;
[0062] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 700° C. and calcining at high temperature for 8 hours; the product of step S2 is recorded as STNOF-Al2O3;
[0063] S3: The product of step S2 and NaCl were mixed in a molar ratio of 1:10, heated to 350°C in an Ar atmosphere, maintained for 48 hours, and then the NaCl was dissolved and removed by adding water, followed by drying at 80°C overnight to obtain a finished tin-based oxyfluoride compound (Sn2TiNbO6F). The product of step S3 was recorded as STNOF-Al2O3-M.
[0064] Example 2
[0065] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0066] S1: 0.404 g SnO (3 mmol), 0.172 g SnF2 (1.1 mmol), 0.160 g TiO2 (2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 30 min to obtain a raw material mixture;
[0067] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 600° C. and calcining for 10 hours; the product of step S2 is recorded as STNOF-Al2O3;
[0068] S3: The product of step S2 and NaCl were mixed in a molar ratio of 1:5, heated to 300°C in an Ar atmosphere, maintained for 24 hours, and then the NaCl was dissolved and removed by adding water, and then dried at 80°C overnight to obtain a finished tin-based oxyfluoride compound (Sn2TiNbO6F). The product of step S3 was recorded as STNOF-Al2O3-M.
[0069] Example 3
[0070] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0071] S1: 0.404 g SnO (3 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 50 min to obtain a raw material mixture;
[0072] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube in a muffle furnace at 780° C. and calcining for 6 hours; the product of step S2 is recorded as STNOF-Al2O3;
[0073] S3: The product of step S2 and NaCl were mixed in a molar ratio of 1:5, heated to 320°C in an Ar atmosphere, maintained for 46 hours, and then the NaCl was dissolved and removed by adding water, followed by drying at 80°C overnight to obtain a finished tin-based oxyfluoride compound (Sn2TiNbO6F). The product of step S3 was recorded as STNOF-Al2O3-M.
[0074] Example 4
[0075] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0076] S1: 0.134 g SnO (1 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol), 0.088 g NaF (2.1 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 30 min to obtain a raw material mixture;
[0077] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 600° C. and calcining at high temperature for 10 hours;
[0078] S3: The product of step S2 and NaCl are mixed in a molar ratio of 1:5, heated to 300°C in an Ar gas atmosphere, maintained for 24 hours, and then the NaCl is dissolved and removed by adding water, and then dried at 80°C overnight to obtain a finished tin-based oxyfluoride compound (NaSnTiNbO5F2).
[0079] Example 5
[0080] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0081] S1: 0.134 g SnO (1 mmol), 0.172 g SnF2 (1.1 mmol), 0.160 g TiO2 (2 mmol), 0.092 g NaF (2.2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 60 min to obtain a raw material mixture;
[0082] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 700° C. and calcining at high temperature for 8 hours;
[0083] S3: The product of step S2 and NaCl were mixed in a molar ratio of 1:10, heated to 350°C in an Ar atmosphere, maintained for 48 hours, and then the NaCl was dissolved and removed by adding water, followed by drying at 80°C overnight to obtain a finished tin-based oxyfluoride compound (NaSnTiNbO5F2).
[0084] Example 6
[0085] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0086] S1: 0.134 g SnO (1 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol), 0.088 g NaF (2.1 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 50 min to obtain a raw material mixture;
[0087] S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 700° C. and calcining at high temperature for 8 hours;
[0088] S3: The product of step S2 and NaCl were mixed in a molar ratio of 1:6, heated to 350°C in an Ar atmosphere, maintained for 30 hours, and then the NaCl was dissolved and removed by adding water, and then dried at 80°C overnight to obtain a finished tin-based oxyfluoride compound (NaSnTiNbO5F2).
[0089] Comparative Example 1
[0090] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0091] S1: 0.404 g SnO (3 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 30 min to obtain a raw material mixture;
[0092] S2: The raw material mixture is placed in a boron nitride crucible, and calcined at 600° C. in a tube furnace for 10 h through argon gas; the product of step S2 is recorded as STNOF-none.
[0093] Comparative Example 2
[0094] A method for preparing a tin-based oxyfluoride compound comprises the following steps:
[0095] S1: 0.404 g SnO (3 mmol), 0.165 g SnF2 (1.05 mmol), 0.160 g TiO2 (2 mmol) and 0.266 g Nb2O5 (1 mmol) were mixed, 5 mL ethanol was added, and the mixture was ground in a mortar for 30 min to obtain a raw material mixture;
[0096] S2: adding the raw material mixture into a quartz glass tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace and calcining at 600° C. for 10 hours; the product of step S2 is recorded as STNOF-SiO2.
[0097] Figure 2 XRD diagrams of STNOF samples synthesized by different preparation methods, the ordinate is the diffraction peak intensity (Intensity); Figure 2 It can be seen that the STNOF samples synthesized by different preparation methods correspond to the standard card PDF-04-001-8271 of Sn2TiNbO6F;
[0098] However, the STNOF-none sample contains relatively more impurities, the sample peak of the impurity in the STNOF-SiO2 sample has a significant decrease, there is no peak corresponding to the obvious impurities in the STNOF-Al2O3 sample, and the main peak intensity of the STNOF-Al2O3-M sample and the STNOF-Al2O3 sample has basically not changed.
[0099] Figure 3 UV-Vis images of STNOF samples synthesized by different preparation methods; Figure 3 It can be seen that the STNOF-none sample contains relatively more defects (corresponding to the strong absorption spectrum of the catalyst sample), the defect density in the STNOF-SiO2 sample is significantly reduced, and the defect density in the STNOF-Al2O3 sample is also relatively low.
[0100] Figure 4 The pictures of STNOF samples synthesized by different preparation methods. Figure 4 It can be seen that the color of the STNOF-none sample is dark red, the STNOF-SiO2 sample is orange-red, and the STNOF-Al2O3 sample is also orange-red.
[0101] Figure 5 Activity diagram of STNOF samples synthesized by different preparation methods; among them:
[0102] Reaction conditions: 0.15 g 0.5 wt% Pt / catalyst; 120 mL water; 30 mL TEOA; 300 W xenon lamp (I=15A; λ≥420 nm);
[0103] Co-catalyst loading: The reduction co-catalyst Pt was loaded on the photocatalyst STNOF by impregnation and hydrogen reduction. Usually, a certain amount of H2PtCl6·6H2O (99.9%, Sinopharm) was added to 2mL of deionized water containing 0.2g of sample. The resulting aqueous solution was ultrasonically treated for five minutes and then stirred and evaporated in a water bath (80°C). After the water was evaporated, the catalyst was collected and heated in a hydrogen-argon mixture with a hydrogen volume fraction of 5% at 200°C (a total of 200mL min -1 ) for 1 hour.
[0104] pass Figure 5 It can be seen that the STNOF-none sample has no hydrogen production activity, the STNOF-Al2O3 sample has about 5 times higher hydrogen production activity than the STNOF-SiO2 sample, and the STNOF-Al2O3-M sample has about 3 times higher hydrogen production activity than the STNOF-Al2O3 sample. The reason for this may be that the defect density in STNOF-Al2O3 is smaller than that in STNOF-SiO2, and the activity is improved;
[0105] Compared with STNOF-Al2O3, STNOF-Al2O3-M may produce new surface substances or remove low-valent metals that are unfavorable for photocatalytic reactions during the molten salt treatment, thereby improving the activity.
[0106] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0107] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a tin-based oxyfluoride compound, characterized in that: The steps include: S1: Mix the raw materials SnO, SnF2, TiO2 and Nb2O5, add ethanol or deionized water, and grind them evenly to obtain a raw material mixture; S2: adding the raw material mixture into a quartz glass tube containing a corundum tube, placing the raw material mixture in the corundum tube, sealing the quartz glass tube, and then placing the sealed quartz glass tube into a muffle furnace at 500-800° C. for calcining for 5-10 hours; S3: treating the product of step S2 with molten salt to obtain the tin-based oxyfluoride compound; The temperature of the molten salt treatment is 300-400°C and the treatment time is 24h-48h; The molar ratio of the product of step S2 to the molten salt is 1:(5-10).
2. The method for preparing a tin-based oxyfluoride compound according to claim 1, characterized in that: The molar ratio of the raw materials SnO, SnF2, TiO2 and Nb2O5 in step S1 is 3:(1.05~1.2):2:
1.
3. The method for preparing a tin-based oxyfluoride compound according to claim 1, characterized in that: The raw materials of step S1 also include NaF, and the molar ratio of the raw materials NaF, SnO, SnF2, TiO2 and Nb2O5 is (2.1-2.2):1:(1.05-1.1):2:
1.
4. The method for preparing a tin-based oxyfluoride compound according to claim 1, characterized in that: The milling time of step S1 is 30 min to 60 min.
5. The method for preparing a tin-based oxyfluoride compound according to any one of claims 1 to 4, characterized in that: The molten salt treatment was performed using an Ar gas atmosphere.
6. The method for preparing a tin-based oxyfluoride compound according to claim 5, characterized in that: The molten salt for the molten salt treatment is selected from at least one of KNO3, KCl, NaNO3, and NaCl.
7. The method for preparing a tin-based oxyfluoride compound according to claim 5, characterized in that: Step S3 also includes washing the sample treated with molten salt with water and then drying it to obtain a finished tin-based oxyfluoride compound.
8. A tin-based oxyfluoride compound, characterized in that: The tin-based oxyfluoride compound is prepared by the method according to any one of claims 1 to 7.
9. Use of the tin-based oxyfluoride compound according to claim 8 as a water decomposition photocatalyst.